Kremlin school of negotiation - Ryzov, Igor; Fleming, Alex (tr.) (Great Britain Canongate Books, 2021)
Negotiating is something that we all do, whether at work or at home. But what if we come across someone who just wont give in? How can we defend ourselves against manipulation? And how do we say no without compromising a deal? Legend has it that the Kremlin school of negotiation was born in Russia in the 1920s, under the rule of Joseph Stalin, and it still has its followers and advocates to this day. Using the official Kremlin method and years of business experience, Igor Ryzov guides us through the most effective techniques in negotiating terms that satisfy both parties. From knowing how to get the most information about a potential deal, to how to read your counterpart, and advice on defusing tension, this comprehensive handbook ensures a mutually acceptable resolution that leaves you walking away successful. With practical examples, and exercises to hone your negotiating skills, The Kremlin School of Negotiation will offer the tools you need to master any deal..
Keywords: Business and Management; Negotion